2017
DOI: 10.1007/s40618-016-0605-7
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of glycated albumin in gestational diabetes mellitus

Abstract: PurposeOur objective was to compare the diagnostic performance of glycated hemoglobin (HbA1c), GA, and fasting plasma glucose (FPG) for the diagnosis of GDM.MethodsWomen at their late second or early third trimesters seen from October 2011 to April 2012 were studied. GDM was diagnosed based on oral glucose tolerance test results, and GA and HbA1c were measured at the same time. Patients were divided into two groups (with and without GDM), and areas under the receiver-operating characteristic curves (AUCs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
4
15
0
2
Order By: Relevance
“…We compared the GlyA levels of pregnant women with and without GDM at the 24-28 weeks of gestation and found no significant difference (P = 0.993) between the two groups. This result was consistent with a study conducted by Zhu et al [22], in which no statistical GlyA difference was observed between the patients with and without GDM. In current practice, GDM was diagnosed during 24-28 weeks of gestations by FPG and postprandial plasma glucose levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We compared the GlyA levels of pregnant women with and without GDM at the 24-28 weeks of gestation and found no significant difference (P = 0.993) between the two groups. This result was consistent with a study conducted by Zhu et al [22], in which no statistical GlyA difference was observed between the patients with and without GDM. In current practice, GDM was diagnosed during 24-28 weeks of gestations by FPG and postprandial plasma glucose levels.…”
Section: Discussionsupporting
confidence: 93%
“…As a non-traditional glycemic marker, the limited diagnostic value of GlyA in GDM has been reported in several articles. Zhu et al [22] reported that the AUC values were 0.726 for FPG and only 0.542 for GlyA in the second trimester. Similar observation was made by Saglam et al [25], with the AUC of GlyA being 0.550 in the GDM diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the GA levels of pregnant women with and without GDM at the 24-28 weeks of gestation and found no significant difference (P = 0.824) between the two groups. This result was consistent with a study conducted by Zhu et al [20], in which no statistical GA difference was observed between the patients with and without GDM who were less than 28 weeks of gestations.…”
Section: Discussionsupporting
confidence: 93%
“…In a study of 114 patients with GDM [22], the cut-off value of GA5.8 %, which was derived from the ROC curve had optimal specificity (100%) and poor sensitivity (17.1%) for diagnosing GDM. Zhu et al [20] reported that the AUC values were 0.726 for FPG and only 0.542 for GA in the second trimester. Similarly, observation was made by Saglam et al [23] with the AUC of GA being 0.550 in the GDM diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, there was no significant increase in the incidence in the group of women with HbA1c of more than 5.7% compared with the group of women with HbA1c of 5.7% or less [20] which suggests that GA is preferable. While it may be better than HbA1c for monitoring diabetes it does not appear to perform better than HbA1c when used for screening [21].…”
Section: Anaemiamentioning
confidence: 97%